STUDY LITERATURE REVIEW: HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT AKAN MANFAAT BUAH OKRA TERHADAP PENYAKIT DIABETES MELLITUS - Mardiana Pratiwi; Jaenudin Jaenudin; Ayu Pratiwi (Universitas Muhammadiyah Ponorogo, 2023)
Measuring blood glucose levels on a regular basis is very important to avoid complications. The okra plant (Abelmoschus escelentus) is a plant that is often used for alternative medicine. This plant is used is the part of the fruit. The purpose of this study was to determine public understanding of the benefits of okra fruit to reduce blood sugar levels for diabetes among the community. This study used the literature review method with PICO criteria and article searches were obtained through online search sites, namely through the Indonesian library site and searches using the form of google scholar, scien direct, and willey. The results show that there is significant public understanding regarding okra knowledge to lower blood sugar levels in people with diabetes mellitus and there is an effect on okra fruit to lower blood sugar levels in diabetes mellitus. Okra fruit is proven to have the benefit of lowering blood sugar levels, besides that okra fruit is easy to get and the price is not too expensive. Non-pharmacological therapy using okra is very good especially for people with diabetes mellitus.